ANALYSIS OF THE MATERIAL-HOUSEHOLD LEXICON REGARDING THE AREAS OF SARIASIYA (TAMADDUN NURI JURNALI, 2024)
In this article, areal linguistic research, the provision of social and everyday vocabulary in the Sario dialects, and some assigned clothing lexemes characteristic of this period in the work of Alisher Navoi are studied and explained with examples.